The law and economics of the data economy: introduction to the special issue - Thomas Eger; Marc Scheufen (European Journal of Law and Economics, 2024)
This article intends to provide a framework to better understand the economic problems and legal challenges resulting from the transition of the European economy to a data economy. We discuss some policy concerns surrounding the data economy, such as concentration in the data economy, anticompetitive business practices in the data economy, access to data and data sharing, data reliability, distributional effects of the data economy, and cybercrime. Moreover, we provide an overview of some important EU legal initiatives and reforms and clarify how the papers in this special issue contribute to assessing these initiatives from an economic point of view.
Keywords: K11; K20; K21; L86; O33; Y20; 340; Digital platforms; Data access; Data sharing; Data reliability